Time-varying optimization of COVID-19 vaccine prioritization in the context of limited vaccination capacity - Shasha Han (Nature Portfolio, 2021)
In the context of limited supply, strategies for optimising allocation of COVID-19 vaccines are needed. Here, the authors explore time-varying strategies that adapt to the epidemiological situation and simultaneously optimise for multiple objectives including reducing numbers of infections, hospitalisations, and deaths.